The project implementation profile's applicability to the modern construction industry - Chiropa, Moses Tinashe (Department of Construction Economics and Management, 2019)
This research evaluated the applicability of the current project implementation profile (PIP) tool to the modern construction industry. The research also aimed to identify any new critical success factors (CSFs) to deliver successful construction projects. The research questions were: a. How applicable are the success factors from the PIP tool in delivering successful modern construction projects? b. Are there other success factors that may be considered for inclusion in the PIP tool for modern construction projects? Critical success factors were identified through a deep literature review. An online webbased questionnaire with the critical success factors was then developed and this tool was utilized to gather data for the research from various project management stakeholders. Collected information was summarized, analyzed and discussed leading to a conclusion. The research identified a revised list of 10 key success factors (KSF) which comprised of 6 non-PIP factors which are: adequate budget; client requirements; competence of project manager; competence of contractors, subcontractors and suppliers; risk management and design and 4 PIP factors which are: client consultation, communication, client acceptance and top management support. From the 20 KSFs that were under investigation, “Adequate budget” was the factor that scored the highest and the lowest scored was “support from other departments.” The research also concluded that the success factors from the existing PIP tool are not sufficient in delivering successful modern construction projects and there are additional success factors that can be considered for inclusion in the PIP tool to aid modern construction projects success. To strengthen the PIP success factors in response to the research questions, it is necessary to execute additional research in this area; in particular the actual questions used by the tool and the assessment framework needs to be revised in light of this research.